Comensalidade e cultura: saberes e sabores nas refeições contemporâneas - Naves, Marcelo (2022)
This dissertation aimed to raise questions about contemporary commensality that can directly and indirectly affect the psyche of the commensal. As support for the theoretical content, the work presented results of extensive observation and field records made in restaurants from different regions and social classes of the State of São Paulo, in order to understand the experiences, attitudes and eating habits of the diners, reserving specific characteristics between lunch and dinner, in addition to meals made on weekdays and business hours versus meals made on weekends. Initially, the work highlighted the importance of the food experience as a sociocultural and civilizing act, capable of defining groups and provoking feelings of belonging and exclusion. To clarify the contemporary characteristics of commensality, the ways of relating today, affected by modernity and globalization, by the accelerated distribution of information easily accessible using the internet, as well as specificities in food and in the ways of eating due to the technological advances and industrialization, as well as changes in eating habits and individualization in the act of eating. With the help of the studies of Claude Fischler and his theory of gastro-anomy, this work sought a psychosocial expansion of the act of eating and sought to understand and highlight what is eaten in addition to food, such as the sharing of personal, regional and cultural experiences. It was necessary to highlight the presence of technology in contemporary commensality, involving the use of appliances during meals and the presence of commensality in the metaverse and in the use of applications related to food. Finally, the work sought to relate the points raised with Psychology and with commensal issues of physical, psychological, emotional and relational health, in search of opening paths for further studies about this relationship so relevant to subjectivity and human development